Cloning and sequencing of the genes for Shiga toxin from Shigella dysenteriae type 1. - Strockbine, N A (1988)
The structural genes for Shiga toxin, designated stx A and stx B, were cloned from Shigella dysenteriae type 1 3818T, and a nucleotide sequence analysis was performed. Both stx A and stx B were present on a single transcriptional unit, with stx A preceding stx B. The molecular weight calculated for the processed A subunit was 32,225, while the molecular weight of the processed B subunit was 7,691. Comparison of the nucleotide sequences for Shiga toxin and Shiga-like toxin I (SLT-I) from Escherichia coli revealed that the genes for Shiga toxin and SLT-I were greater than 99% homologous; three nucleotide changes were detected in three separate codons of the A subunits. Only one of these codon differences resulted in a change in the amino acid sequence: a threonine in Shiga toxin at position 45 of the A subunit compared with a serine in the corresponding position in SLT-I. Furthermore, Shiga toxin and SLT-I had identical signal peptides for the A and B subunits, as well as identical ribosome-binding sites, a putative promoter, and iron-regulated operator sequences. These findings indicate that Shiga and SLT-I are essentially the same toxin. Southern hybridization studies with total cellular DNA from several Shigella strains and internal toxin probes for SLT-I and its antigenic variant SLT-II showed that a single fragment in S. dysenteriae type 1 hybridized strongly with the internal SLT-I probe. Fragments with weaker homology to the SLT-I probe were detected in S. flexneri type 2a but no other shigellae. No homology between the Shiga-like toxin II (SLT-II) probe and any of the Shigella DNAs was detected. Whereas SLT-I and SLT-II are phage encoded, no phage could be induced from S. dysenteriae type 1 or other Shigella spp. tested. These results suggest that the Shiga (SLT-I) toxin genes responsible for high toxin production are present in a single copy in S. dysenteriae type 1 but not in other shigellae. The findings further suggest that SLT-II genes are absent in shigellae, as are toxin-converting phages.